Grammatical Errors in Writing Recount Texts (A Case Study at The First Year of Senior High School) - Nunung Prasetyo; Andang Saehu; Hanna Sundari (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Writting in a foreign language is one of the most difficult abilities in learning language skills. The problem occurred because understanding grammatical knowledge and rewording sentence writing was lowering frequency by students. This research aimed to investigate grammatical errors made by students and analyze the causes of language interface errors in writing recount text. Thirty respondents were chosen purposively to be involved in this study. The data collection instruments were conducted by writing text and conducting interviews under causes of grammatical errors.  Results from the study revealed that 11 distinct grammatical errors were present in the students' writing: word and sentence level errors. The most prevalent grammatical errors at the word level are tense verb errors 69 (35.38%), and punctuation has 39 (20%) problems. Further, 18 (9.23%) word choice problems followed that. In the meantime, the causes of errors were determined to be intralingual (0.22%) and interlingual (0.7%) errors. It implemented that the teacher should be offered an explanation and correction of any grammatical errors made by students, as well as comments regarding whether or not students were successful in learning English writing material and need more practice.